Językowe konceptualizacje czynności autoerotycznych. Rekonesans lingwistyczno-kulturowy - Skowronek, Bogusław (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2014)
Linguistic conceptualisations of autoerotic activities. Linguistic and cultural reconnaissance Article discusses linguistic conceptualisations of autoerotic activities-sexual sphere rejected culturally and linguistically, mostly in European culture. Analyses of particular linguistic forms taken from dictionaries and the Internet, are based on a broad cultural and ideological background according to methodological principles of cultural linguistics. There was especially shown an influence of religion and ideology, locating sexual activities in the field of medicine. Those discourses still “command” semiotically and linguistically of the term of autoerotism. Analysis of collected verbal constructions has shown that semantic field of autoerotism contains following elements: 1. official names (found in dictionaries); 2. Socially fixed neutral euphemisms; 3. fixed periphrases with different degree of formality (from vulgar, through colloquial and in everyday use to those used jokingly); 4. periphrases created on occasions which are the most common, also with different degree of formality.